Mating Behavior of Hansen’s Bush Frog (Chiromantis hansenae) at Sakaerat Environmental Research Station, Northeastern Thailand - Taksintum, Wut; Lauhachinda, Virayuth; Boonsoong, Boonsatien (Agriculture and Natural Resources, 2012)
The inﬂ uence of meteorological and ecological factors on the breeding of Hansen’s bush frog, Chiromantis hansenae was investigated during October 2008 to September 2009 at the Sakaerat Environmental Research Station, Northeastern Thailand. Meteorological factors (air temperature, relative humidity and rainfall) were analyzed using an ordination method. The principal component analysis output indicated a correlation between mating behavior (amplexus, laying egg behavior and advertisement calls) and termination of rainfall; however, reproduction was prolonged and lasted through the entire rainy season. While the temperature showed a signiﬁ cant relationship with mating behavior (a higher temperature resulted in an increase in mating), humidity did not appear to inﬂ uence the mating. In Northeastern Thailand the breeding habitat of these frogs is in ponds. Male frogs advertise from elevated branches of trees and shrubs hanging over the water body including stems of grasses around the pond. Females normally attach eggs on leaves and take care of them until the eggs hatch.